TRANSFORMING AGRICULTURE IN THE DIGITAL AGE: A LITERATURE REVIEW ON INNOVATION, VALUE CHAIN INTEGRATION, AND FARMER EMPOWERMENT - Mahidin Fahmie; Solehan (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
The rapid advancement of digital technologies has fundamentally reshaped agricultural systems, transforming traditional farming practices into data-driven, technology-enabled, and market-oriented production models. This transformation is driven by innovations such as precision agriculture, artificial intelligence (AI), Internet of Things (IoT), blockchain, and digital platforms, which collectively enhance productivity, resource efficiency, and market connectivity. This study aims to systematically review and synthesize existing scholarly literature on agricultural transformation in the digital age, with a particular focus on technological innovation, value chain integration, and farmer empowerment. Employing a qualitative library-based research approach, this study analyses peer-reviewed publications indexed in major academic databases, including Scopus, Web of Science, and Google Scholar. A thematic content analysis is applied to identify dominant research themes, conceptual frameworks, and empirical patterns. The findings reveal that digital innovation significantly improves farm-level productivity and sustainability, while digital value chain integration enhances supply chain efficiency, transparency, and market access. Furthermore, digital tools play a crucial role in empowering farmers by expanding access to knowledge, financial services, and high-value markets, thereby strengthening livelihoods and economic resilience. However, the review also identifies persistent challenges related to digital inequality, infrastructure gaps, regulatory fragmentation, and unequal access to innovation, particularly among smallholder farmers and marginalized groups. These constraints may limit the inclusiveness and long-term sustainability of digital agricultural transformation. This study contributes to the literature by providing an integrative conceptual synthesis that connects technological, economic, and social dimensions of agricultural transformation. The findings offer important insights for policymakers, development practitioners, and agribusiness stakeholders in designing inclusive, resilient, and competitive agricultural development strategies in the digital era.